Ambiente de control y acciones logísticas en la Municipalidad Distrital de Teniente Manuel Clavero - Putumayo, durante el año 2021 - Ramirez Rios, Gary Ñivinson (2023)
The current investigation entitled: Verification Environment (control) and Logistics Operations in Teniente Manuel Clavero - District Municipality of Putumayo 2021 merits the following question: For this reason, is there an eloquent agreement between the control environment and logistics operations in Teniente Manuel Clavero - Municipality District of Putumayo 2021? The general objective is to establish an eloquent correspondence between the controlled environment and logistics operations in the Teniente Manuel Clavero-Putumayo District Municipality during 2021. The method is a descriptive design, at a composite, non-empirical and cross-sectional level. The research model was created with 10 similar employees in supplies in the city of analysis. Likewise, the plurality of employees of the logistics district of the municipality of Teniente Manuel Clavero-Putumayo by 2021 understand that the control environment maintains a normal percentage of 60% and the logistics operation maintains a high level of 95%. The final analysis revealed that they maintained an eloquent correspondence through the control environment and logistics operations in the Teniente Manuel Clavero-Putumayo District Municipality in 2021.